The Capital Budgeting Process: Incentives and Information - HARRIS, MILTON; RAVIV, ARTUR (Journal of Finance, 1996)
ABSTRACT We study the capital allocation process within firms. Observed budgeting processes are explained as a response to decentralized information and incentive problems. It is shown that these imperfections can result in underinvestment when capital productivity is high and overinvestment when it is low. We also investigate how the budgeting process may be expected to vary with firm or division characteristics such as investment opportunities and the technology for information transfer.